A cross-validation study of the college learning effectiveness inventory (CLEI) - Yeager, Mary Elizabeth Bratton (Kansas State University, 2009)
This study examines the validity of the College Learning Effectiveness Inventory (CLEI). The CLEI is a new instrument designed to assess issues that college students face that affect their performance, including academic success and persistence. The CLEI serves diagnostic and prescriptive functions. Academic advisors, counselors and others whose work involves supporting student success and retention can use the CLEI to assess an individual student’s strengths and weaknesses and use the results to counsel students and provide appropriate remedial activities. This study compares the following six scales of the College Learning Effectiveness Inventory (CLEI) with instruments that have already been established. The six scales of the CLEI are as follows: (1) Academic Self-Efficacy, (2) Organization and Attention to Study, (3) Stress and Time Pressure, (4) Involvement with College Activity, (5) Emotional Satisfaction, and (6) Class Communication. The validation instruments for this cross-validation study included the Concentration, Self-Testing, Study Aids, and Time Management scales from the Learning and Study Strategies Inventory (LASSI), the Time Organization and Study Environment Management subscale of the Motivated Strategies for Learning Questionnaire (MSLQ), the College Adjustment Questionnaire (CAQ), the Rosenberg Self-Esteem Scale (RSES), and the Student Propensity to Ask Questions (SPAQ) scale. This study answers the following research questions: 1.) Are the CLEI scales reliable measures of the constructs they purport to assess? 2.) Are the CLEI scales valid measures of the dimensions they purport to assess? 3.) What are the CLEI scales attributes for this sample, and how do they compare with those from an earlier normative sample? 4.) How are the CLEI scales related to one another? 5.) Are the CLEI scales gender neutral? and 6.) Does the CLEI differentiate between students who are successful and those who may be at risk? Finally, this study cross-validates the CLEI. The reason for a cross-validation study of new scales is to demonstrate that these new measures actually measure what they purport to assess. Without cross validation, we would have to rely on a scale’s face validity, which is a comparatively weak method of assessing validity.
Keywords: Learning; Education, Educational Psychology (0525)